Secrets of tracing your ancestors : get the scoop on America's # 1 hobby : do-it-yourself genealogy! - Quillen, W. Daniel (New York : Cold Spring Press, 2010)
Presents a guide for novice genealogy researchers that covers techniques used by professionals, with examples, tips about a variety of resources such as military records and the Internet, and instructions on how to write an engaging life history.
Why genealogy? -- Get started -- Get organized -- What's in a name? -- Vital records -- Genealogical societies -- Genealogical collections in libraries -- Computers and the Internet -- Using the LDS church -- Census records -- Military records -- Ethnic research -- Who am I? -- Using DNA as a research tool -- Is anyone out there? -- Professional genealogists -- Help your descendants! -- In summary
Keywords: GENEALOGY